(untitled) (Third Sector Social Economic Review, 2024)
Cooperatives are unions of individuals that have different characteristics from associations and companies with their traditional structure, aiming not to make and share profits but to “improve the economy of the individual” through cooperation between each other. From this perspective, it can be seen that the “trust” relationship between the parties forming the cooperative union is an important structure. Audit is the most important tool to further strengthen this trust relationship between the parties that make up the cooperative union and to provide assurance to non-cooperative parties affected by cooperative activities. External audit in cooperatives is carried out by professional auditors. External audit studies in cooperatives, as in companies that make financial reporting, focus on compliance with the legislation affecting financial reporting and to what extent the financial statements reflecting the economic results reflect the real situation of the cooperative. The Ministry of Trade has determined the procedures and principles regarding the inspection of cooperatives and their parent organizations and the authorization of unions and central unions for inspection with the “Regulation on the Inspection of Cooperatives and Parent Organizations”. In this study, the regulations regarding the external audit of cooperatives in the said Law and Regulation are explained by comparing them with the regulations regarding independent audit.